(untitled) (Fiep Bulletin - online, 2012)
The objective was to analyze the levels of habitual physical activity and lifestyle of academics at the Federal Universityof Alagoas - Campus Arapiraca. It is a character study of a cross-sectional descriptive and quantitative approach with a sample of88 subjects, 48 male and 40 female, duly registered in the period 2010.2. We used the Questionnaire of Habitual Physical ActivityQuestionnaire and Profile of the Single Lifestyle, proposed and validated by Nahas (2001). The results showed that females aremore inactive than the males, and in relation to the profile of individual lifestyle, every group had scores between one and two forNutrition (1.23), physical activity (1.17), preventive behavior (1.79) Relations (1.94) and stress management (1.57). It isrecommended to conduct research to assess levels of habitual physical activity and lifestyle of college students by identifying theindividual results separately by sex and travel.